2007
DOI: 10.1177/0002716206298694
|View full text |Cite
|
Sign up to set email alerts
|

Capital, Consumption, Communication, and Citizenship: The Social Positioning of Taste and Civic Culture in the United States

Abstract: In this article, the authors analyze the field of cultural consumption in the United States. Using the 2000 DDB Lifestyle Study, they examine a cross-section of Americans in terms of their occupational categories, media usage, consumption practices, social behaviors, and indicators of civic and political engagement. In doing so, the authors find many parallels to the determinants of taste, cultural discrimination, and choice within the field structure observed by Bourdieu in 1960s French society. However, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 17 publications
1
20
0
1
Order By: Relevance
“…In the past, when the survey was collected by mail, its response rate was between 70 and 80% (Cafferata, Horn, & Wells, 1997). A number of studies using DDB Worldwide Communications Group's Life Style TM survey data are published in reputable journals (e.g., DuttaBergman & Wells, 2002;Friedland et al, 2007;Lee, 2005a;Shah, Kwak, & Holbert, 2001). Putnam's (2000) influential book, Bowling Alone, which described in part the influence of media in the decline of collective social activities, used this series of survey along with the highly respected General Social Survey, and suggested that their quality is comparable.…”
Section: Methodsmentioning
confidence: 99%
“…In the past, when the survey was collected by mail, its response rate was between 70 and 80% (Cafferata, Horn, & Wells, 1997). A number of studies using DDB Worldwide Communications Group's Life Style TM survey data are published in reputable journals (e.g., DuttaBergman & Wells, 2002;Friedland et al, 2007;Lee, 2005a;Shah, Kwak, & Holbert, 2001). Putnam's (2000) influential book, Bowling Alone, which described in part the influence of media in the decline of collective social activities, used this series of survey along with the highly respected General Social Survey, and suggested that their quality is comparable.…”
Section: Methodsmentioning
confidence: 99%
“…6 Despite a lengthy history of debate, empirical investigation of the relationship between consumption and civic participation is just beginning. 7 Work by Keum and colleagues, for example, categorizes consumptive behavior into two types, socially conscious and status conscious, and provides evidence that both types of consumption were positively associated with civic participation. 8 Yet the mixed literature with regard to the consumer-citizen link still suggests that the relationship might be contingent upon individual differences and social circumstances.…”
mentioning
confidence: 99%
“…Reconhecendo a importância cada vez maior das mulheres na sociedade brasileira e o grande aumento no nível de escolaridade feminino, nos últimos anos (FRIEDLAND et al, 2007) e, seguindo a metodologia adotada por Macedo (2014), foram incorporadas a escolaridade e a ocupação da mãe na metodologia aqui utilizada. No entanto, salienta-se que o status conferido a um diploma de uma universidade federal ou particular renomada seja mais qualificado e, portanto, na quantificação do capital cultural esse fator foi considerado.…”
Section: Metodologiaunclassified